Liberia : Strategic Policy Options for Medium Term Growth and Development - Dessus, Sébastien; Hoffman, Jariya; Lofgren, Hans (World Bank, Washington, DC, 2013)
The objective of this paper is to inform Liberia's medium-term growth and development strategy for 2012-17 and its National Vision: Liberia Rising 2030, both of which are under preparation. The analysis is based on MAMS (Maquette for MDG [Millennium Development Goal]) Simulations, a computable general equilibrium model. A base scenario (designed to represent a central case for the evolution of Liberia's economy up to 2030) is compared to a set of non-base scenarios that introduce alternative assumptions for the mining sector, government spending on infrastructure and human development, as well as foreign borrowing. The simulations, which cover the period 2012-2030, indicate that rapid expansion of mining output, front-loaded investment in infrastructure, and improved government efficiency may bring about rapid growth. The findings underscore the importance of allocative and operational efficiency of public spending. It is also important that the government balance spending on infrastructure and human development as they complement each other and face different constraints. Spending on infrastructure tends to have relatively strong and immediate growth and poverty reduction effects, whereas spending on human development has a stronger positive impact on non-poverty MDG indicators at the cost of lowered economic growth in the short to medium terms. It is important to consider that growth driven by rapid mining expansion entails drawbacks and risks, including the persistence of an enclave economy that will not benefit the majority of the population, and increased vulnerability to fluctuations in iron ore world prices.